Rancang Bangun Alat Pengering Andaliman dengan Menggunakan Metode Quality Function Deployment (QFD) - Benedikta Anna haulian Siboro; Rizal Horas Manahan Sinaga; Devis Wawan Saputra Simanjuntak (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2019)
Andaliman is a typical seasoning plant of Sumatra which can be used as a flavouring traditional Batak (arsik) and other derivative products such as crackers, bandrek which have a taste of andaliman. One process that is passed so that Andaliman can be used as a seasoning and other product is drying process. Generally, andaliman drying is done by solar power or dryer. The current condition at the UMKM of Taman Eden 100 is the length of time of drying and limited capacity so that it is unable to meet the demand of arsik instant flavor. This research was conducted by applying the Quality Function Deployment (QFD) method through a questionnaire distributed to owners and workers at the UMKM to determine the desirable desiccant needs. The results of the QFD are mapped into the House of Quality which is expected to be a picture of the new dryer. From this HOQ, it is produced that the user wants a dryer with a larger capacity than before which has a heat control device so that the heat is evenly distributed in the drying chamber. The aroma of andaliman also remains even though the water content in dry andaliman has decreased.